2015
DOI: 10.4049/jimmunol.1500708
|View full text |Cite
|
Sign up to set email alerts
|

ERK1-Based Pathway as a New Selective Mechanism To Modulate CCR5 with Natural Antibodies

Abstract: Natural human Abs, recognizing an epitope within the first extramembrane loop of CCR5 (the main HIV coreceptor), induce a long-lasting internalization (48 h) of the protein, whereas all known CCR5 modulating molecules show a short-term kinetics (60–90 min). Despite extensive studies on the regulation of CCR5 signaling cascades, which are the effect of concomitant CCR5 internalization by exogenous stimuli such as Abs, downstream signaling continues to be poorly understood. In this article, we report a hitherto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…We analyzed a time course of anti-CCR5 Abs-induced signaling pathway after depleting cellular levels of β-arrestin1 or -2 or both by nucleofecting siRNAs specific to each isoform. The experiments were performed in the T lymphoblastoid R5-SupT1-L23 cell line, which has a CCR5 cell surface level and an activation status comparable to human CD4+ T lymphocytes2124. The activation status of the cells has been evaluated by flow cytometry and the mean fluorescence (MFI) obtained with anti-CD38 antibody was 54.5 and 34.5 respectively, as previously reported21.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We analyzed a time course of anti-CCR5 Abs-induced signaling pathway after depleting cellular levels of β-arrestin1 or -2 or both by nucleofecting siRNAs specific to each isoform. The experiments were performed in the T lymphoblastoid R5-SupT1-L23 cell line, which has a CCR5 cell surface level and an activation status comparable to human CD4+ T lymphocytes2124. The activation status of the cells has been evaluated by flow cytometry and the mean fluorescence (MFI) obtained with anti-CD38 antibody was 54.5 and 34.5 respectively, as previously reported21.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has recently demonstrated that CCR5 specific antibodies (CCR5 Ab Pos), found in Long Term HIV infected subjects (LTNPs), induce a long lasting internalization of the receptor (48 h) mediated by G-protein-dependent ERK1 activity, both in R5-SupT1-L23 and in CD4+ T lymphocytes21. Instead, other groups have demonstrated that when CCR5 internalization is mediated by RANTES, the level of receptor on the cell surface recovered to nearly 100% after 120′ incubation42223.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations